NOTES TOWARDS A POLITICS OF "AMERICAN" CRITICISM - Bové, Paul (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
A meditation on the nature of oppositional criticism and the problems of opposition within and to the discipline and discourse of "American Studies".